Dongeng sebagai Media Pembelajaran Bahasa dan Sastra Indonesia di SD/MI - Komper Wardopo (IAINU Kebumen, 2019)
Fairy tales or folktale are part of the story of rayat (folklore). Every region in Indonesia has many stories of folklore and fairy tales that contain aspects of culture, education, character and high moral values. In order to safeguard and inherit the value of local wisdom and the value of education to the next generation, fairy tales are very feasible to be used as a medium for learning Indonesian language and literature at the basic education level, especially in Elementary Schools (SD) and Madrasah Ibtidaiyah (MI). This article aims to discuss and explain: (1) The potential for diversity of tales as part of folklore spread in various places is the socio-cultural wealth of the community. (2). Fairy tales can be used as a medium for learning Indonesian language and literature in elementary and MI basic education. (3) Fairy tales can be a means of improving literacy culture among elementary and MI students.